MODEL OUTCOME LEARNING ACCOUNTING TAXATION (CASE STUDY OF STUDENTS IN ACCOUNTING STUDY PROGRAM, BANDAR LAMPUNG UNIVERSITY) - Septi Ayu Lestari Habeahan; Riswan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Higher education is useful to be able to develop human resources and has become one of the main focuses in developed countries around the world. Due to the increasing development of today's times, undergraduate graduates are strived to become more qualified and have more knowledge, including insight into tax accounting. The purpose of this study is to find out the factors that affect learning outcomes. The existence of this research was carried out for the method used is a quantitative method with an explanatory research approach that uses as many as 81 samples of students from the class of 2020 and 2021 accounting study programs, Faculty of Economics and Business. The technique for data analysis used in this study is multiple linear regression and using SPSS software to process it. The results of the research obtained showed a positive and significant influence on the variables of understanding taxation and the intensity of assignment on tax accounting learning outcomes. Then the role of motivation in moderating each variable can strengthen the relationship.